Nilai-Nilai Dalam dan Luar Keluarga pada Film “Nanti Kita Cerita Tentang Hari Ini” Karya Angga Dwimas Sasongko - Diva Putri Lasmoro; Aris Arif Mundayat (Universitas Sebelas Maret (UNS), 2025)
Mass media is a means of disseminating information and communication, one of which is film. Movies are very interesting media because they combine audio and visual. Not only does it provide entertainment, but also as an informative moral message, history, and solutions to themes that develop in society. This research was conducted with the aim of knowing the values inside and outside the family represented socially in the movie “Nanti Kita Cerita Tentang Hari Ini” by Angga Dwimas Sasongko. The research method used descriptive qualitative method with the unit of analysis of the scenes in the movie Nanti Kita Cerita Tentang Hari Ini. This research uses Serge Moscovici's Social Representation Theory. The results of this study show values from inside and outside the family that are qualified in the concepts of anchorage, objectivation, and naturalization. Then there are concepts that do not exist in Serge Moscovici's social representation theory, namely de-objectivation and de-naturalization.